The effect of nutrition on the ovulation rate and number of follicles, during one year, of hairy sheep of Northeast Brazil - Silva, Antonio Emídio Dias Feliciano; Foote, Warren C.; Riera, Simon G.; Unanian, Maria Marina (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this study was to determine the ovarian activity of Morada Nova, Santa Inês and Brazilian Somalis hairy breed ewes. Seventy two animals were divided in two groups, G I and G II, 36 each, and placed on two nutritional treatments: confinement and native pasture. These groups were again arranged in a factorial design (3x2) according to the breeds. During one year the ewes were submitted to monthly endoscopy to verify the presence of follicles and luteal phase. The ewes of Morada Nova breed showed a higher ovulation rate (P<0.0001), frequency (P<0.05) number of follicles (P<0.05) and multiple ovulations (P<0.05) than those of Santa Inês and Brazilian Somalis. The sheep mantained on native pasture presented a better ovulation rate (P<0.001) than those of confinement. Similare differences could be observed between the rainy and dry seasons. During the rainy season no differences were observed between the breeds. The determination of the rate and frequency of ovulation, during a year, enabled better understanding of the potential of the sexual activity of the hairy sheep of Northeast Brazil.